THE ENHANCEMENT OF SYMBOLIC LANGUAGE SKILL AND CONCEPT MASTERY IN REDOX REACTION BY NUMBERED HEAD TOGETHER LEARNING MODEL - Eva Setyawati; Nina Kadaritna; Ila Rosilawati (Jurnal Pendidikan dan Pembelajaran Kimia, 2012)
The objectives of this research are to describe effectiveness of Numbered Head Together (NHT) learning model in redox reaction in improving symbolic language skill and to describe effectiveness of NHT learning model in redox reaction material in improving concept mastery.  Population in this research was all Grade X students in State Senior High School 1 Buay Bahuga in academic year 2011/2012. Samples were classroom X2 as experiment classroom and classroom X1 as control classroom. Samples were selected using purposive sampling. This reserach used quasi experiment menthod with Non Equivalent (Prestest and Posttest) Control Group Design). The effectiveness of NHT learning model was measured based on significant n-gain differences of symbolic language skill and concept mastery between NHT learning classroom and conventional learning classroom. The results showed that the average of n-gain of symbolic language skill for experiment and control clasrooms were 0.26 and 0.18 respectively, and the average n-gain of concept mastery for experiment and control classrooms were 0.29 and 0.23 respectively.  Based on hypothesis test, classroom with NHT learning model had higher symbolic language skill and concept mastery than classroom with conventional learning. This indicated that NHT learning was effective in improving symbolic language skill and concept mastery of redox reaction.Keywords: Numbered Head Together (NHT) Learning Model, symbolic language skill and concept mastery